Pengaruh Peran Kepala Sekolah terhadap Mutu Pendidikan Di SMKN Se-Kabupaten Blora - Dian Novika Dewi; Ngasbun Egar; Rosalina Br Ginting (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The quality of education in State Vocational High Schools in Blora Regency is still not optimal. This study was conducted to analyze the influence of the principal's role on the quality of education. The study used a quantitative approach with an ex post facto type. The study population was 383 State Vocational High School teachers in Blora Regency, with a sample of 196 teachers through proportional random sampling. The data collection instrument was a Likert scale questionnaire, and data analysis was carried out using simple and multiple linear regression with the help of SPSS 29. The role of the principal has a positive and significant effect on the quality of education, although its contribution is relatively small. The R² value of 0.082 indicates that the role of the principal only contributes 8.2% to improving the quality of education, while 91.8% is influenced by other factors. The dominant dimensions of the principal's role are as an administrator (90%), creator of school climate (88.4%), and educator (87.2%). Although the quantitative contribution of the principal's role to the quality of education is low, qualitatively it is still considered important and strategic. Improving the quality of education requires synergistic support from teachers, facilities and infrastructure, school management, and cooperation with parents and the community.